Denken over poëzie en vertalen De dichter Cees Nooteboom in vertaling - Schyns , Désirée (Lage Landen Studies, 2018)
This volume of Lage Landen Studies has a twofold purpose: on the one hand we want to pay attention to the scholarly work on the Dutch author Cees Nooteboom, in particular to his poetry in translation which has hardly received any academic attention yet, and on the other hand we would like to contribute to trends in Translation Studies which focus on agency, subjectivity, intention, translators poetics and creativity in translated texts. Indeed, in the last decade the focus of Translation Studies has shifted to the translator who plays such an important role in the circulation of cultural products nowadays. In this volume the contributions not only focus on Nooteboom's poems in translation, but also on Nooteboom as a translator of poetry himself, again a subject which has hardly been studied yet. The first part opens with an introduction on Nooteboom's poetry by Susanne Schaber, editor of the Gesammelte Werke at Suhrkamp Verlag in Germany. In the second contribution of this section Ton Naaijkens gives a plea for intuition and creativity in scholarly work on translation. The second section deals with Cees Nooteboom as a translator of poetry. Esther Op de Beek, who contributed together with Nooteboom on the book Avenue (fifteen years of world literature), highlights the position of Nooteboom as a cultural mediator. Stéphanie Vanastens contribution analyses this mediation position with the help of a concrete case study of two French poets translated and presented by Nooteboom to the Dutch and Flemish public of Avenue. Yves T'Sjoen addresses methodological issues for translation scholars who want to study the work of writer-translators such as Claus and Nooteboom. In the last section, the translated poetry of Nooteboom forms the centre of the contributions. Jane Fenoulhet focusses on four English translations of the poem 'Bashō', Stefaan Evenepoel on two translations of 'Leeftocht' and in the round table discussion translators Ard Posthuma, David Colmer, Irinia Michajlova and Philippe Noble discuss their translators' choices with the poet Cees Nooteboom. In his afterword the poet reflects on the round table and the symposium in Ghent in November 2016 which formed the exciting starting point for this volume.